Expanding the Diet for DIET: Electron Donors Supporting Direct Interspecies Electron Transfer (DIET) in Defined Co-Cultures - Wang, Li-Ying; Nevin, Kelly P.; Woodard, Trevor L.; Mu, Bo-Zhong; Lovley, Derek R. (Frontiers in Microbiology, 2016)
Direct interspecies electron transfer (DIET) has been recognized as an alternative to interspecies H2 transfer as a mechanism for syntrophic growth, but previous studies on DIET with defined co-cultures have only documented DIET with ethanol as the electron donor in the absence of conductive materials. Co-cultures of Geobacter metallireducens and Geobacter sulfurreducens metabolized propanol, butanol, propionate, and butyrate with the reduction of fumarate to succinate. G. metallireducens utilized each of these substrates whereas only electrons available from DIET supported G. sulfurreducens respiration. A co-culture of G. metallireducens and a strain of G. sulfurreducens that could not metabolize acetate oxidized acetate with fumarate as the electron acceptor, demonstrating that acetate can also be syntrophically metabolized via DIET. A co-culture of G. metallireducens and Methanosaeta harundinacea previously shown to syntrophically convert ethanol to methane via DIET metabolized propanol or butanol as the sole electron donor, but not propionate or butyrate. The stoichiometric accumulation of propionate or butyrate in the propanol- or butanol-fed cultures demonstrated that M. harundinaceae could conserve energy to support growth solely from electrons derived from DIET. Co-cultures of G. metallireducens and Methanosarcina barkeri could also incompletely metabolize propanol and butanol and did not metabolize propionate or butyrate as sole electron donors. These results expand the range of substrates that are known to be syntrophically metabolized through DIET, but suggest that claims of propionate and butyrate metabolism via DIET in mixed microbial communities warrant further validation.